1969
DOI: 10.1037/h0028009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic desensitization and relaxation of high-test-anxious secondary school students.

Abstract: This study was designed to answer two questions: (1) Is the systematic desensitizaion of test anxiety effective with secondary school students?; (2) Is rehxation per se as useful a technique as systematic desensitization? High test anxious secondary-school students were assigned to one of two experimental conditions, desensitization or relaxation, and met for 20 minutes daily for a period of 6 weeks. Their results were compared to those of a no treatment control group. It appeared that the experimental subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Test anxiety: Of 29 RCTs, those using wait‐list controls or other controls found that relaxation is more effective, and the rest found it to be as effective as other behavioural therapies for test anxiety, such as systematic desensitisation, rational emotive therapy, biofeedback, rehearsal and skills acquisition, and meditation. 203 ‐ 231…”
Section: Resultsmentioning
confidence: 99%
“…Test anxiety: Of 29 RCTs, those using wait‐list controls or other controls found that relaxation is more effective, and the rest found it to be as effective as other behavioural therapies for test anxiety, such as systematic desensitisation, rational emotive therapy, biofeedback, rehearsal and skills acquisition, and meditation. 203 ‐ 231…”
Section: Resultsmentioning
confidence: 99%
“…In all of these studies, dependent measures of anxiety showed improvement in treated compared with non-treated populations; however, results were by no means consistent and reports (Laxer, Quarter, Kooman and Walker, 1969;Laxer and Walker, 1970) suggest that various measures of anxiety were differentially affected, with manifest anxiety measures, usually self-reported showing the greatest change (Andrews, 1971;Johnson, Tyler, Thompson and Jones, 1971;Laxer et al, 1969) and physiologic measures somewhat less (Barabasz, 1973;Kondas, 1967). Tests of school performance documented improved marks in three of six studies (Deffenbacher, 1974;Mann and Rosenthal, 1969;Mann, 1972).…”
Section: Sub-clinical Studiesmentioning
confidence: 89%
“…The closer the subjects' behavior approached the unequivocably pathologic realm, the more resistant to specific intervention it appears to become. In the sub-clinical studies desensitization was able to alleviate test and speech anxiety and increase performance in intelligence tests, GPA's or reading tests in most investigations, but was not successful in three others (Andrews, 1971;Laxer et al, 1969;Laxer and Walker, 1970). Within the clinical group the findings became less convincing -in two out of the three studies desensitization was shown to be more effective than no treatment controls in the short term but in the excellent studies by Miller (1972) and Hampe (1973) the treatments offered little advantage over the control waiting period by the end of the second year.…”
Section: Efficacymentioning
confidence: 97%
See 1 more Smart Citation
“…However, most studies show that the benefits of relaxation training are limited to anxiety reduction. Laxer and colleagues compared the efficacy of relaxation training and systematic desensitisation in the treatment of test anxious secondary school students (Laxer, Quarter, Kooman & Walker, 1969). Relative to notreatment controls, both conditions resulted in significant declines in self-reported anxiety.…”
Section: Test Anxietymentioning
confidence: 99%